Hydrodynamic behaviour in liquid-liquid flow system: bench scale study - Mohd Hafiz, Razak @ Ali (2013)
The purpose of this study is to determine hydrodynamic properties of liquid-liquid systems between ethanol and palm oil. The fundamental characteristics of dispersed phase are essentially controlled by Sauter diameter and coalescence rate. Droplets of oil in ethanol phase were dropped several. Besides, size of droplets and dropping velocity were measured. From the average, the Sauter diameter is 0.002m with 0.73m/s velocity under gravitational force. Ethanol is potentially to be dispersed phase in agitated environment as compared to the palm oil. Other than that, several phase ratios were also mixed under vigorous stirring (700 rpm) for 20 minutes before settling process taking place. The times of settlement shows that, at the high oil ratio the appearance of emulsion become significant. This implies that the emulsion although may create ultimate contact between phases and it might also have mass transfer hindrance to the liquid-liquid system because dynamic density.